Fever of unknown origin: an unexpected diagnosis (Portuguese Journal of Family Medicine and General Practice, 2021)
Introduction: Fever of unknown origin (FUO) syndrome is defined as the presence of temperature higher than 38.3 °C lasting more than three weeks, with failure to reach a diagnosis despite a correct investigation in three outpatient visits or three days in the hospital. It implies a criterion evaluation for general practitioners, leading to a proper diagnostic investigation. Between the large spectrum of possible etiologies, the HIV infection is a possibility to consider, especially if there are associated risk factors.Case Description: Female, 47 years old, Caucasian, with a history of neoplasm of the cervix submitted to conization four years ago. She is a smoker. Divorced, she belongs to a mono-parental family since 2005, her last partner was eight years ago. The patient came to an urgent consultation with symptoms of malaise, fatigue, evening fever, and dry cough, for several weeks. After the first steps of investigation, the etiology remained undefined, despite the recurrence of symptoms. Given the clinical condition of FUO syndrome, it was performed a wider etiologic investigation revealed HIV-1 positive serology. The patient was referred to an infectious diseases hospital appointment and started on antiretroviral treatment and therapy directed to pneumocystosis, and acquired immunodeficiency syndrome (AIDS)-defining disease. This diagnosis had a profound influence at a personal, family, and social level with the need for follow-up in psychology and psychiatry consultation.Commentary: The etiologic investigation of FUO syndrome, in this clinical case, has conducted to an unexpected diagnosis of AIDS, which has sensitized the health team to the importance of a timely HIV screening, for the correct approach of the FOI syndrome and for the importance of longitudinal monitoring by the family physician.
Keywords: HIV infection; Acquired immunodeficiency syndrome; Fever of unknown origin; Pneumocystosis